173k views
1 vote
Which expression is equivalent to -9x^-1y^-9/-15x3y-3? Assume x & y ≠ 0

Which expression is equivalent to -9x^-1y^-9/-15x3y-3? Assume x & y ≠ 0-example-1

1 Answer

4 votes

Explanation:

when we have multiplications of fractions, we can simply "break" the multiplications apart, simplify every fraction, and then combine the results again.

-9/-15 = 3/5

x^-1/x⁵ = 1/x¹x⁵ = 1/x⁶

y^-9/y^-3 = y³/y⁹ = 1/y⁶

so, when we multiply the 3 fractions again, we get

3/(5x⁶y⁶)

which is the second answer option.

User Marijus
by
5.2k points